B cells and Autoimmunity - Pillai, Shiv (2011)
There is a growing appreciation for the role for B cells in autoimmune disorders in which inflammation is driven by T cells, in addition to the well-established role for B cells in autoimmune disorders characterized by pathogenic auto-antibodies. Current information on tolerance checkpoints in B cells, B cell depletion, BAFF blockade, regulatory B cells and clonal ignorance mediated by the SIAE/Siglec pathway will be reviewed.